Berbisnis Cerdas Di Era Digital Untuk Siswa-Siswi SMK Global Prima Islamic School Bekasi - Jayanti Apri Emarawati; Yunita Sari; Essy Malays Sari Sakti; Erwin Suhandono (Universitas Persada Indonesia YAI, 2023)
Along with advances in information technology, trends in the business world are also increasingly varied.Having a little knowledge of information technology, business and management, but if you are familiar with computersand have access to the internet, it is actually enough to be the basic capital to run a business via the internet. One ofthe trends in the business world by utilizing information technology is digital marketing. The concept and applicationof digital marketing is something that is done to boost product sales from a brand. As we know, the acceptance oftechnology and the internet in society is very broad, so it is not surprising that digital marketing activities are the mainchoice by companies. As a result, companies compete with each other to create interesting content to display in theirmarketing in cyberspace. The number of digital marketing used by companies, proves that digital has many advantagesand benefits that can be obtained. By implementing a digital marketing strategy, the business can run according to themarketing plan. Easy and practical management will save time and effort, so it will be more focused on businessdevelopment plans.